PROFESSIONAL EXAMINATIONS A Department for Students of Accounting. - Chamberlain, Henry T. (The Accounting Review, 1945)
Abstract The article presents problems that were prepared by the Board of Examiners of the American Institute of Accountants and were presented as the second half of the C.P.A. Examination in accounting practice held in May, 1945. The examinees were allowed four and a half hours to solve both problems. One of the question required the students to prepare a summary statement of executors as to principal, showing assets remaining in the estate and a summary statement of executors as to income of the estate of Ben East, deceased from the information as of September 30, 1944. Another question was to prepare a statement showing the estimated cost of producing 13,500 tons of X product for the purpose of bidding on a government contract of Dart Co. from the information provided. Dart Co. manufactures X, a main product, and Y, a by-product. X is produced and sold by the ton (2,000 pounds.). The raw material used in production consists of three ingredients, "H," "I," and "J". The contract for 13,500 tons of X represents 60% of the budgeted 1945 production of X by Dart Co.